Alteration of m6A epitranscriptomic tagging of ribonucleic acids after spinal cord injury in mice - Ni, Shuangfei; Luo, Zixiang; Fan, Yonggang; Zhang, Weixin; Peng, Wei; Zhang, Huafeng (Frontiers in Neuroscience, 2022)
The m6A methylation is reported to function in multiple physiological and pathological processes. However, the functional relevance of m6A modification to post-spinal cord injured (SCI) damage is not yet clear. In the present study, methylated RNA immunoprecipitation combined with microarray analysis showed that the global RNA m6A levels were decreased following SCI. Then, gene ontology (GO) and kyoto encyclopedia of genes and genomes (KEGG) analyses were conducted to demonstrate the potential function of differential m6A-tagged transcripts and the altered transcripts with differential m6A levels. In addition, we found that the m6A “writer,” METTL3, significantly decreased after SCI in mice. The immunostaining validated that the expression of METTL3 mainly changed in GFAP or Iba-1+ cells. Together, this study shows the alteration of m6A modification following SCI in mice, which might contribute to the pathophysiology of the spinal cord after trauma.